Psychological capital has a positive correlation with humanistic care ability among nurses - Liu, Xiaohong; Li, Cuiping; Yan, Xiaoting; Shi, Bingqing (Frontiers in Psychology, 2022)
Objective: With the improvement in health awareness, humanistic care ability of nurses has become a focus of public attention. The aim of the study was to confirm the relationship between psychological capital and humanistic care ability of nurses, and to provide suggestions on improving the humanistic care ability of nurses. Methods: A cross-section survey was conducted. Three hundred thirty-nine nurses were recruited from a tertiary general hospital in Taizhou, China. Psychological capital and humanistic care ability were measured using a self-reported questionnaire. Correlation analysis and stepwise multiple regression analysis were performed to analyze the correlation between psychological capital and humanistic care ability. Results: The psychological capital and humanistic care ability scores were 91.57±13.96 and 189.08±20.37, respectively. Differences in psychological capital scores across professional titles (F=4.88, p=0.01), departments (F=3.69, p<0.001), years of work (F=4.68, p<0.001), and marital status (t=3.25, p<0.001) were statistically significant. There were statistical differences for the humanistic care ability scores among nurses based on marital status (p=0.01). The total psychological capital scores and the four sub-dimensions scores were positively correlated with the humanistic care ability scores among nurses. Self-efficacy was the main predictor of nurses' humanistic care ability. Conclusion: Psychological capital positively affected the humanistic care ability of nurses. Self-efficacy was the main predictor of humanistic care ability. Nursing managers can formulate strategies from the perspective of positive psychology to improve humanistic care ability of nurses.